Community partners' perceptions in working with local health departments: an exploratory study. (1st January 2013) - Barnes, Priscilla; Curtis, Amy; Downey, Laura Hall; Ford, Leigh
The purpose of this article is to explore perceptions of partnerships among organisational representatives and volunteers working with local health departments (LHDs). Semi-structured interviews were conducted, transcribed and coded in NVIVO 8.0. Using thematic analysis, four major themes were identified. Partners' reported multiple roles in the partnerships, but did not express a desire to play more of a leadership role. Motivations to partner differed depending if they were personal or organisational driven to participate. Partners in rural communities reported partnering more often due to limited financial resources and staff, but were more concerned about burnout. Indicators of success reported by partners included building strong relationships, completing projects, measuring attendance to events, and to a smaller extent, change in community outcomes using assessments. Results suggest LHD partners are not interested in increased leadership responsibility in their partnerships and that motivations to partner need to be considered in improving population health status.